Quality of life and Physical Activity after Total Knee Arthroplasty in Elderly Women - Tsonga, Θεανώ; Michalopoulou, Μαρία; Malliou, Παρασκευή; Godolias, Γεώργιος (Inquiries in Physical Education and Sport, 2008)
The aim of this study was to examine the magnitude of changes in health-related quality of life of patients with knee osteoarthritis before, 3 and 6 months after total knee arthroplasty and to determine the changes in physical activity and in the number of steps taken at the same period. The patients were 26 elderly women (M=73±6.1years) with knee osteoarthritis undergoing primary knee arthroplasty. The research lasted 11 months. Health-related quality of life, physical activity, pain and function as well as the number of steps were assessed before, 3 and 6 months after the procedure. The instruments used were the Medical Outcomes Study Short Form (SF-36), the Physical Activity Scale for the Elderly (PASE) and the pedometer SW200 Digiwalker of Yamax. According to the results of ANOVA repeated measures, patients showed a significant improvement (p< .01, η2 =.22) in health–related quality of life, particularly in physical function, (p< .001) bodily pain (p< .001) and vitality scale (p< .001) of SF-36, 3 and 6 months after the procedure. Physical activity (PASE score) increased at 3 and 6 months after the arthroplasty (p< .001, η2 =.41), and the number of steps increased 6 months after, compared to the assessment that took place 3 months after the procedure (p< .001). Consequently, elderly patients that participated in this study benefited significantly in most aspects of their life after the total knee arthroplasty. The improvements took place gradually and up to 6 months post operatively and lead to the conclusion that total knee arthtoplasty may improve several aspects of quality of life of patients and physical activity participation in a short period of time.